Unstable Temperature Distribution in Friction Stir Welding - Aziz Hussein, Sadiq; S., Thiru; Izamshah, Raja; Md Tahir, Abd Salam (Hindawi Publishing Corporation, 2014)
In the friction stir welding process, a nonuniform and high generated temperature is undesirable. Unstable temperature and distribution affect thermal and residual stresses along the welding line, thus necessitating mitigation. This paper presents a simple method to prevent significant temperature difference along the welding line and also to help nullifying some defect types associated with this welding, such as end-hole, initial unwelded line, and deformed areas. In the experimental investigation, a heat and force thermocouple and dynamometer were utilized while couple-field thermomechanical models were used to evaluate temperature and its distribution, plastic strain, and material displacement. The suggested method generated uniform temperature distributions. Measurement results are discussed, showing a good correlation with predictions